Behavior Management Based on Higher Order Thinking Skills; An Analysis of Learning Innovation - Fadlillah Fadlillah (Journal of Research in Educational Management, 2023)
The complexities of life issues require thinking skills that go beyond mere application of learned knowledge. Learners should be more creative in generating solutions to the problems they encounter in their daily lives. Higher Order Thinking Skills (HOTS) are implemented at School through an internalized learning system manifested in the form of activities, programs, and behavioral patterns within the boarding school environment. This effort aims to shape students' character, develop their knowledge and insights, enhance motivation, encourage positive, creative, critical, and independent thinking behaviors. Therefore, this research aims to understand the forms and impacts of learning innovation based on Higher Order Thinking Skills. This study employs a qualitative approach, specifically a case study design. Data collection techniques include interviews, observations, and documentation. The findings of this research indicate that: 1) the innovation in the learning system based on Higher Order Thinking Skills (HOTS) is carried out through behavioral patterns, doctrinal patterns, development of Furudhul ‘Ainiyah, and organizational cultural patterns. The impact of the innovation in the PAI learning system based on Higher Order Thinking Skills (HOTS) includes high motivation to engage in positive activities and a strong desire to become independent and accomplished individuals.